Hunger is suppressed after resistance exercise with moderate-load compared to high-load resistance exercise: The potential influence of metabolic and autonomic parameters - Freitas, Marcelo Conrado [UNESP]; Panissa, Valéria Leme Gonçalves; Lenquiste, Sabrina Alves; Serra, Fernanda de Maria; Figueiredo, Caique [UNESP]; Lira, Fabio Santos [UNESP]; Rossi, Fabricio Eduardo (Canadian Science Publishing, 2020)
The purpose of present study was to compare the effects of moderate-load versus high-load resistance exercise (RE) on hunger response, blood lactate, glucose, and autonomic modulation in trained men, and to examine the correlations between these parameters. For this, 11 recreationally resistance-trained males performed 2 randomized trials: moderate-load (6 sets at 70% 1-repetition maximum (1RM) and a 90-s rest interval between sets) and high-load (6 sets at 90% 1RM and a 180-s rest interval between sets) leg-press exercise until movement failure. The subjective rating of hunger was obtained through a visual analog scale. Glucose and lactate concentration were evaluated at rest, immediately after exercise, and 30 min after exercise. Heart rate variability was recorded at baseline and during recovery (until 30 min after exercise) to assess autonomic modulation. The moderate-load condition induced lower subjective hunger ratings than the strength condition immediately after exercise (19.7 ± 16.6 vs 47.3 ± 27.7 mm), 30 min after exercise (33.6 ± 22.9 vs 58.5 ± 29.9 mm), and 60 min after exercise (43.8 ± 26.6 vs 67.8 ± 27.9 mm) (p < 0.05) and lower area under the curve hunger in relation to the high-load condition (p < 0.006). Moderate-load RE presented greater lactate concentration and induced slower heart rate variability recovery in relation to high-load RE (p < 0.05), but no difference was found in glucose, as well as no correlations between any of the variables investigated. In conclusion, moderate-load RE induced lower subjective hunger ratings, slower recovery of the parasympathetic nervous system, and higher lactate concentration in relation to high-load RE, but the metabolic variables were not correlated with hunger suppression.
Keywords: Appetite; Heart rate variability; Lactate; Maximal strength; Resistance strength; Strength exercise